2013
DOI: 10.1111/febs.12543
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear phosphoinositides and their impact on nuclear functions

Abstract: Polyphosphoinositides (PPIn) are important lipid molecules whose levels are de‐regulated in human diseases such as cancer, neurodegenerative disorders and metabolic syndromes. PPIn are synthesized and degraded by an array of kinases, phosphatases and lipases which are localized to various subcellular compartments and are subject to regulation in response to both extra‐ and intracellular cues. Changes in the activities of enzymes that metabolize PPIn lead to changes in the profiles of PPIn in various subcellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
78
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(80 citation statements)
references
References 135 publications
(157 reference statements)
2
78
0
Order By: Relevance
“…T he existence of nuclear, nonmembrane pools of signaling phosphorylated derivatives of phosphatidylinositols or phosphoinositides (PIP n ) was reported over two decades ago (1)(2)(3). Consistent with these early reports, lipid-modifying enzymes responsible for phosphoinositide metabolism were also found in the nucleus (4)(5)(6)(7); however, the function of PIP n in this cellular compartment remains poorly defined. The nuclear receptors (NRs) steroidogenic factor 1 (SF-1, NR5A1) and liver receptor homolog 1 (LRH-1, NR5A2) bind phosphoinositides as well as other phospholipids in their large hydrophobic pockets (8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 81%
“…T he existence of nuclear, nonmembrane pools of signaling phosphorylated derivatives of phosphatidylinositols or phosphoinositides (PIP n ) was reported over two decades ago (1)(2)(3). Consistent with these early reports, lipid-modifying enzymes responsible for phosphoinositide metabolism were also found in the nucleus (4)(5)(6)(7); however, the function of PIP n in this cellular compartment remains poorly defined. The nuclear receptors (NRs) steroidogenic factor 1 (SF-1, NR5A1) and liver receptor homolog 1 (LRH-1, NR5A2) bind phosphoinositides as well as other phospholipids in their large hydrophobic pockets (8)(9)(10)(11)(12)(13).…”
mentioning
confidence: 81%
“…They are products of 3′, 4′ and 5′ phosphorylation on the inositol in all of the possible combinations of the structural lipid phosphatidylinositol. These molecules are localized along the secretory and endocytic pathways, as well as in the nucleus in eukaryotes (Shah et al, 2013). They regulate various structural and developmental functions in all eukaryotic models, such as membrane biogenesis, lipid homeostasis, vesicular trafficking, and cytoskeleton organization and dynamic (D'Angelo et al, 2008;Ischebeck et al, 2010;Saarikangas et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Reports from several laboratories have demonstrated the role of PIP 2 in modulating various nuclear functions (3,31). It might be argued that the nuclear presence of PIP5K is obvious to produce PIP 2 .…”
Section: Discussionmentioning
confidence: 99%
“…PIP5K is a 61-kDa protein migrating at about 68 kDa in SDS-PAGE (2). Although classical phosphoinositide signaling is concentrated in the plasma membrane, recent studies have suggested the presence of a distinct phosphoinositide signaling in the nucleus (3). PIP 2 in the nucleus has been mapped onto detergent-insoluble fractions co-localizing with small nuclear ribonucleoprotein particles in nuclear speckles (4) and at electron-dense structures (5), suggesting its involvement in pre-mRNA processing.…”
mentioning
confidence: 99%